PENANAMAN KARAKTER RELIGIUS OLEH LEMBAGA NON-FORMAL (STUDI KASUS BIMBINGAN DAN KONSULTASI BELAJAR NURUL FIKRI) - Rahmi Juwita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Education is identical to school (formal institutions), while non formal institutions are still neglected as one of the sub-systems in the world of education. Meanwhile, one of the non-formal institutions for “Bimbingan dan Konsultasi Belajar” (Study Guidance and Consultation) Nurul Fikri is a tutoring institution that intensively implements religious character values. This study aims to describe internalizes of the values of religious character education in students by learning guidance institutions. This research uses a qualitative approach with the type of case study research. The selection of informants was carried out by purposive sampling. The data obtained were analysed using the interactive analysis model of Huberman with the steps of reducing data, displaying data, and retrieving data. The results of the study describe the form of internalization of religious character values in BKB NF, namely: 1) The existence of BIP subjects as a forum for Muslim personality development; 2) Leaders, teachers and staff become role models in BKB NF; 3) The norms and values of the BKB NF Padang institution make all BKB NF Padang residents try to carry out God's orders and stay away from His prohibitions. The implications of this research can be used for education offices and educational institutions related to the character-building model in non-formal institutions.